Does transanal total mesorectal excision (taTME) result in better quality of life and functional outcomes than traditional TME does?: a retrospective propensity score-adjusted cohort study : research - Ammann, Yanic Rolf; Klein, Marie; Marti, Lukas; Warschkow, René; Ströse, Lennard; Sparn, Moritz; Jäger, Tarkan; Bischofberger, Stephan; Brunner, Walter (Langenbeck's archives of surgery, 2025)
Purpose The improved prognosis of rectal cancer through modern therapeutic approaches raises questions regarding quality of life (QoL) and functional outcomes. In this study, we compared post-transanal total mesorectal excision (taTME) short- and long-term QoL and functional outcomes with those after abdominal TME (abTME). Methods Prospective data from patients who underwent elective taTME or abTME for stage I-III rectal cancer followed by anastomosis were retrospectively propensity score-adjusted. The primary endpoint, QoL, was assessed with the European Organization for Research and Treatment of Cancer core questionnaire (EORTC QLQ-C30). Functional outcomes were the secondary endpoints. Results Among 494 patients during 2013-2022, 187 patients who underwent taTME and 62 patients who underwent abTME were included. QoL was worse after taTME at isolated time points: overall QoL (after 3 years: 72 vs. 82 points, p = 0.017) and QLQ-total (after 3 years: 81 vs. 87 points, p = 0.028; after 4 years: 82 vs. 89 points, p = 0.012). After propensity score matching, the between-group differences were still significant but smaller: overall QoL − 6 points, p = 0.021; QLQ-total − 5 points, p = 0.026. Conclusion The differences reported at isolated time points have questionable clinical relevance. Therefore, taTME and traditional abTME seem to have comparable long-term QoL and functional outcomes. Clinical trial registration ClinicalTrials.gov, NCT06505863, https://clinicaltrials.gov/search?id=NCT06505863 .